2017
DOI: 10.1073/pnas.1708345114
|View full text |Cite|
|
Sign up to set email alerts
|

Gut microbiomes and reproductive isolation in Drosophila

Abstract: Experimental studies of the evolution of reproductive isolation (RI) in real time are a powerful way in which to reveal fundamental, early processes that initiate divergence. In a classic speciation experiment, populations of were subjected to divergent dietary selection and evolved significant positive assortative mating by diet. More recently, a direct role for the gut microbiome in determining this type of RI in has been proposed. Manipulation of the diet, and hence the gut microbiome, was reported to resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 52 publications
4
73
1
Order By: Relevance
“…This outcome contrasts with earlier reports demonstrating a major role for the microbiota in fly mate choice 35,36 . The current observations are in line with recent work finding that diet-induced microbial changes did not alter mate choice 37 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This outcome contrasts with earlier reports demonstrating a major role for the microbiota in fly mate choice 35,36 . The current observations are in line with recent work finding that diet-induced microbial changes did not alter mate choice 37 .…”
Section: Discussionsupporting
confidence: 93%
“…In these studies, dietary shifts were used to perturb microbiota compositions over multiple generations. In contrast, a recent report failed to detect a role for the Drosophila microbiota in mating preferences after dietary shifts and antibiotic exposure 37 . To test whether direct microbe removal impacts microbiota-dependent attractiveness, conventional male flies were placed in a chamber together with decapitated GF and CV female bodies, and their courtship was monitored for 60 minutes (Figure 6 A).…”
Section: Microbe Removal Has Little Impact On Activity or Sleepmentioning
confidence: 87%
“…A remarkable and puzzling observation was that the effect of diet on assortative mating, and its prevention by antibiotic treatment, was effectively instantaneous, indicating a direct effect of the presence of the bacteria. However, other studies showed that neither the significant positive assortative mating by diet, nor the involvement of gut bacteria in this process, is consistent within or across different Drosophila strains either instantaneously or across generations …”
Section: A Role For Gut Microbiome Symbionts In Driving Host Ri In Drmentioning
confidence: 92%
“…The development of sequencing technologies has enabled rich descriptions of the communities of non‐culturable as well as culturable bacteria that are found on or in different hosts and in novel ecological niches . One increasing area of interest has been the relationships between hosts and their commensal gut microbes …”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, assortative mating preferences by diet have been proposed to result from correlated dietary traits. Specifically, it was suggested that feeding flies of the same strain different diets significantly altered their gut microbiota, changing pheromone mating signals as a result (Rosenberg, Zilber-Rosenberg, Sharon, & Segal, 2018;Sharon et al, 2010), although subsequent studies failed to replicate resulting patterns of diet-based assortative mating (Leftwich et al, 2017). Furthermore, when diet-based assortative mating has been detected so far, it has been limited to inbred, not outbred, Drosophila strains (Najarro, Sumethasorn, Lamoureux, & Turner, 2015).…”
mentioning
confidence: 99%